Internacionalização de empresas via consórcio de exportação - Langoski, Leandro Márcio (Universidade do Vale do Rio do Sinos, 2007)
There are approximately five millions of small companies in Brazil. Among them, the majority have no knowledge on international markets. Until recently, only large companies sought to develop actions related to internationalization. Today, small businesses also are seeking this type of opportunity through exports to different countries. It is well known that the scarcity of financial resources, skilled people and information are constraints for these companies. However, those constraints may be overcome through strategic alliances. This study aims to analyze the internationalization of an export consortium from the furniture industry located in the state of Rio Grande do Sul, Brazil. The export consortium is a type of strategic alliance. One of this objective is to face shared problems. The research method was a case study. We interviewed: the chairman and the sales manager of the consortium; two directors and two export managers from the companies of the consortium; and two directors of companies that no lo
Keywords: consórcio de exportação; móveis; internacionalização; consortium of exportation; furniture industry; internationalization; Ciências Sociais Aplicadas